1999
DOI: 10.1136/adc.81.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of asthma, rhinitis, and atopic eczema: the north east study

Abstract: Using the international study of asthma and allergies in childhood (ISAAC) questionnaire, 3000 children aged 6-7 years from various schools in the north east of England were studied. In this population, the lifetime prevalence rates of various symptoms and diagnoses were: wheezing, 29.6%; atopic eczema, 27.8%; rhinitis, 23.1%; and self reported asthma, 22.7%. Rhinitis was reported by 44% and 40% of boys and girls with asthma, respectively. Atopic eczema was reported by 46% of both boys and girls with asthma. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
31
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 27 publications
10
31
1
Order By: Relevance
“…In older boys, aged 13-14, only asthma was more prevalent than in girls [9]. Similar findings were revealed in cross--sectional surveys in England, which found a higher prevalence of allergic rhinitis in prepubertal males [10,11]. One of the most seminal studies was performed in Scotland and involved a population sample of 266,733 [12].…”
Section: Discussionsupporting
confidence: 72%
“…In older boys, aged 13-14, only asthma was more prevalent than in girls [9]. Similar findings were revealed in cross--sectional surveys in England, which found a higher prevalence of allergic rhinitis in prepubertal males [10,11]. One of the most seminal studies was performed in Scotland and involved a population sample of 266,733 [12].…”
Section: Discussionsupporting
confidence: 72%
“…Environmental factors have been thought to be important in determining the subsequent development of asthma [24]. One of the most important extrinsic factors that influence children's health is passive smoking [25][26][27]. The association between passive smoking and asthma in childhood is well known.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional study of the UK general population reported a prevalence of asthma of 12% [1]. The prevalence of asthma is even higher in children; the prevalence rate of reported asthma was 23% in British children aged 6–7 years [2], and 21% in those aged 12–14 years [3]. …”
Section: Introductionmentioning
confidence: 99%